The Development of Halal Ecotourism Destination. Context of Business Collaboration and Mutual Trust - MUDOFIR, MUDOFIR; SUSILO, Priyo; DIHARTO, Awan Kostrad; MUAFI, MUAFI; BADAWI, BADAWI (Journal of Environmental Management and Tourism; Vol 9 No 2 (2018): JEMT Volume IX Issue 2(26) Spring 2018, 2018)
Halal ecotourism destination is become a strategic issue that is worth to be studied. Halal ecotourism appear as a concept synergized between ecotourism and halal tourism. This research aims to analyze the importance of business collaboration in managing halal ecotourism destination by maintaining the mutual trust. This research is conducted using qualitative method through interview with some of the manager of ecotourism in DIY and Central Java Province. The research result also supported with photos, documentation, and cross check of secondary data with field data. The validity and reliability test is done using reference study, data comparison, and consultation with experts. The result concluded that the development of halal ecotourism destination will be successful if the manager can have business collaboration between institutions and maintain the mutual trust, so that the visits of domestic or foreign tourists will increase.